2020
DOI: 10.48550/arxiv.2012.07922
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Probing ultrafast laser plasma processes inside solids with resonant small-angle X-ray scattering

Abstract: Extreme states of matter exist throughout the universe e.g. inside planetary cores, stars or astrophysical jets. Such conditions are generated in the laboratory in the interaction of powerful lasers with solids, and their evolution can be probed with femtosecond precision using ultra-short X-ray pulses to study laboratory astrophysics, laser-fusion research or compact particle acceleration. X-ray scattering (SAXS) patterns and their asymmetries occurring at X-ray energies of atomic bound-bound transitions cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Studying solids upon high-intensity laser irradiation allows to observe and learn about plasma dynamics that have impact on a wide variety of applications such as tumor therapy [1][2][3][4], fusion research [5][6][7][8] or laboratory astrophysics [9,10]. Previous studies have shown, that a specific target design can optimize the laser-target interaction towards preferred mechanisms like rear particle acceleration [11,12], front surface compression [13][14][15] or bulk heating [16,17]. Following this approach, we present a computational study of multi-layered (ML) targets to study and enhance specifically the target heating.…”
Section: Introductionmentioning
confidence: 99%
“…Studying solids upon high-intensity laser irradiation allows to observe and learn about plasma dynamics that have impact on a wide variety of applications such as tumor therapy [1][2][3][4], fusion research [5][6][7][8] or laboratory astrophysics [9,10]. Previous studies have shown, that a specific target design can optimize the laser-target interaction towards preferred mechanisms like rear particle acceleration [11,12], front surface compression [13][14][15] or bulk heating [16,17]. Following this approach, we present a computational study of multi-layered (ML) targets to study and enhance specifically the target heating.…”
Section: Introductionmentioning
confidence: 99%